Continuity of active commuting to school across two generations: the Cardiovascular Risk in Young Finns Study - Suominen, Tuuli H; Kukko, Tuomas; Yang, Xiaolin; Pahkala, Katja; Rovio, Suvi; Hirvensalo, Mirja; Kähönen, Mika; Raitakari, Olli; Tammelin, Tuija H; Salin, Kasper (Oxford University Press (OUP), 2026)
Active commuting to school (ACS) may markedly contribute to overall physical activity (PA) among youth, but ACS levels have declined in recent decades. Parents significantly influence their children’s PA and commuting behaviours, and lifestyle habits are often transferred from parents to offspring. This study investigated whether parents’ ACS during their youth was associated with their offspring’s ACS at similar ages. In this study, 660 parent–offspring pairs self-reported their mode of school commuting: parents during 1980–86 (generation G1, ages 9–18, 53% female) and offspring in 2018 (generation G2, ages 7–20, 52% female). A path model was constructed to examine the association of ACS in G1 with ACS in G2, adjusted for generation-specific covariates (distance to school, school grade, gender, living area, parental education, and family income). Standardized path coefficients are reported, concentrating on their direction and relative strength. Distance to school was inversely associated with ACS in both generations (β ≤ −0.75; SE = 0.03; P < .001). Family income was directly associated with ACS in G1 (β =  0.18; SE = 0.05; P < .01). ACS in G1 was directly associated with ACS in G2 (β =  0.14; SE = 0.05;P < .01). A positive, albeit modest, link was found between parents’ ACS during their youth and their offspring’s ACS at similar ages, after adjusting for multiple important covariates. This intergenerational link could inform public health initiatives to foster sustainable and healthy commuting behaviours that benefit current and future generations. Ensuring accessible distances to school remains important.